2020
DOI: 10.3998/mjcsloa.3239521.0026.113
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the Impact of Impact: Evaluating Community-Campus Engagement as Contextual, Relational, and Process Based

Abstract: As community-campus engagement (CCE) continues to gain momentum, impact has increasingly been evaluated through qualitative measurements rooted in community-based perspectives. However, for CCE to have meaningful impact, it must challenge dominant power structures and work to create equitable relationships. This article explores efforts to better understand and evaluate the impacts of CCE. Based in our research on 12 place-based CCE projects that aimed to support food sovereignty in Canada, the findings highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Beyond conferences and meetings, Hub co-leads, research assistants and partners also worked collectively to analyze and document successful CCE principles and practices with food movements. These learnings have been reflected upon, debated, and shared through academic papers, book chapters, webinars, and conference presentations (for example, see Andrée et al, 2016;Levkoe et al, 2016;Kepkiewicz et al, 2017;Kepkiewicz et al, 2018;Levkoe et al, 2019aLevkoe et al, ' 2019bLevkoe and Kepkiewicz, 2020). Together, all these activities have promoted a genuine recognition that knowledge generated in community and academic circles has a different but equal value.…”
Section: Food Sovereignty Hubmentioning
confidence: 99%
“…Beyond conferences and meetings, Hub co-leads, research assistants and partners also worked collectively to analyze and document successful CCE principles and practices with food movements. These learnings have been reflected upon, debated, and shared through academic papers, book chapters, webinars, and conference presentations (for example, see Andrée et al, 2016;Levkoe et al, 2016;Kepkiewicz et al, 2017;Kepkiewicz et al, 2018;Levkoe et al, 2019aLevkoe et al, ' 2019bLevkoe and Kepkiewicz, 2020). Together, all these activities have promoted a genuine recognition that knowledge generated in community and academic circles has a different but equal value.…”
Section: Food Sovereignty Hubmentioning
confidence: 99%
“…Participatory techniques already have the potential to be relational, requiring cooperation and diverse stakeholders to work together, who significantly benefit from existing social networks (Janzen et al 2016;Kemmis and McTaggart 2005). Levkoe and Kepkiewicz (2020) performed a pan-Canadian evaluation of 12 community engagement initiatives and concluded that after participatory research projects, partners perceived other partnering organizations as better colleagues and friends working towards a common goal and agreed that the process broadened networks, leading to future collaborative works.…”
Section: Intentional Connection Building In Parmentioning
confidence: 99%
“…However, relationships and connections are difficult to anticipate, explain, and evaluate, which can come at direct odds with the bias among funding agencies' criteria to evaluate investments by citing measurable, observable, and quantifiable change, which is equated to impact in final reports. (Hardy et al 2018;Levkoe and Kepkiewicz 2020). Hardy et al's (2018) case study of Hermosas Vidas is unique in that it seeks to quantify the number of 'lasting' relationships built through the participatory health research project.…”
Section: Intentional Connection Building In Parmentioning
confidence: 99%
“…The value and impact of research collaborations cannot be quantified in a straightforward way (Beckman et al, 2011;Greenhalgh et al, 2016;Levkoe & Kepkiewicz, 2020).…”
Section: Intersectoral Research Collaboration and Food Systems Schola...mentioning
confidence: 99%
“…Through the Community First, Impacts of Community Engagement (CFICE) partnership project, partners working on food sovereignty projects described the establishment of a community of practice that contributed to research, teaching, and action. Levkoe and Kepkiewicz (2020) explain:…”
Section: Intersectoral Research Collaboration and Food Systems Schola...mentioning
confidence: 99%